Pneumococcal Endocarditis, Rare but Not Forgotten - Sajjad Ali; Paul Kim; Sorabh Dhar (Annals of Internal Medicine: Clinical Cases)
Pneumococcal endocarditis incidence has significantly decreased since the advent of antibiotics but remains a significant cause of mortality and morbidity in high-risk groups, such as those with heart disease, chronic lung and liver disease, smoking, diabetes mellitus, and immunosuppression. We present a unique case of pneumococcal endocarditis with no clinical stigmata of infective endocarditis that manifested with acute hypoxic respiratory failure and severe aortic regurgitation. A large vegetation on the aortic valve was noted during surgery, with negative blood cultures and aortic valve tissue cultures but positive Streptococcus pneumoniae urinary antigen and polymerase chain reaction (PCR) test on the aortic valve.